Günter Brus’ «Zerreißprobe» und die Tradition christlicher Selbstopfer (Studia austriaca, 2013)
This article addresses the relation of Zerreißprobe (1970), the last performance work of the Viennese Actionist Günter Brus, to the tradition of Christian self-sacrifice. Three aspects of this relation are given particular attention: the aestheticization of suffering, the representative function of sacrifice and the distinction between the dependent body and the postulate of free will.